Biofortified Crops Generated by Breeding, Agronomy, and Transgenic Approaches Are Improving Lives of Millions of People around the World - Garg, Monika; Sharma, Natasha; Sharma, Saloni; Kapoor, Payal; Kumar, Aman; Chunduri, Venkatesh; Arora, Priya (Frontiers in Nutrition, 2018)
Biofortification is an upcoming, promising, cost-effective and sustainable technique of delivering micronutrients to a population that has limited access to diverse diets and other micronutrient interventions. Unfortunately, major food crops are poor sources of micronutrients required for normal human growth. The manuscript deals in all aspects of crop biofortification which includes- breeding, agronomy and genetic modification. It tries to summarize all the biofortification research that has been conducted on different crops. Success stories of biofortification include lysine and tryptophan rich quality protein maize (World food prize 2000), Vitamin A rich orange sweet potato; (World food prize 2016) generated by crop breeding, oleic acid, and stearidonic acid Soybean enrichment; through genetic transformation and selenium, iodine and zinc supplementation. The biofortified food crops, especially cereals, legumes, vegetables and fruits are providing sufficient levels of micronutrients to targeted populations. Although a greater emphasis is being laid on transgenic research, the success rate and acceptability of breeding is much higher. Besides the challenges biofortified crops hold a bright future to address the malnutrition challenge.